Optical Janus film, preparation method and application thereof

By using an optical Janus film in solar water evaporation technology, the dual heat transfer mode of heat conduction and radiation is achieved using the unique structure of its upper and lower surfaces, the problem of low heat utilization in traditional technology is solved, and the water evaporation efficiency and solar light utilization are improved Rate.

CN118788159BActive Publication Date: 2025-02-25INST OF MODERN PHYSICS CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410981266.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-02-25
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

In the existing solar water evaporation technology, the heat utilization rate is low. Traditional photothermal water evaporation heats the water as a whole, and the heat cannot be effectively utilized at the gas-liquid interface.

Method used

An optical Janus film is adopted, with a metal coating on the upper surface and an irregular polymer cone structure, and a radiation heating function on the lower surface, realizing a dual heat exchange mode of heat conduction and heat radiation.

Benefits of technology

It improves the utilization rate of solar light and heat transfer efficiency, enhances the water evaporation efficiency, and the flexibility of the optical Janus film can be applied to non-flat surfaces, and the preparation method is simple and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118788159B_ABST
    Figure CN118788159B_ABST
Patent Text Reader

Abstract

The present application relates to an optical Janus film, a preparation method and its application, wherein the upper and lower surfaces of the optical Janus film have micro-nano structures of different sizes, wherein the micro-nano structures include irregular polymer cones and cone holes formed between the irregular polymer cones; wherein the upper surface has a metal coating. The upper surface of the optical Janus film of the present invention has the characteristic of selective absorption of sunlight, and the lower surface has a radiation heating function. When used for solar water evaporation, it has a dual heat exchange mode of heat conduction and heat radiation, which can improve the utilization rate of sunlight and the heat transfer efficiency; and the optical Janus film of the present application is flexible, applicable to non-flat surfaces, and the preparation method is simple, and large-scale preparation can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material technology, and in particular to an optical Janus film, a preparation method and application thereof. Background Art

[0002] Although 70% of the Earth's surface is covered by water, only 3% is fresh water. Fresh water shortage is one of the biggest threats to sustainable development of the global economy, and with the intensification of environmental pollution, population growth and rapid development of the world economy, the situation has become more serious.

[0003] To this end, researchers have proposed a variety of seawater desalination methods, including reverse osmosis, electrodialysis, thermal distillation and membrane distillation, but these are all high-energy consumption methods that will increase greenhouse gas emissions. In order to meet the urgent need to provide fresh water at the lowest energy consumption, solar water evaporation and seawater desalination methods based on it have developed rapidly in recent years. As early as more than 2,000 years ago, the Greek philosopher Aristotle proposed the method of using solar energy to heat salt water and condense water vapor to obtain fresh water. With the development of modern science and technology, a variety of nanoscale photothermal materials are used to efficiently capture sunlight and convert it into thermal energy, making solar-assisted water evaporation one of the most promising seawater desalination and sewage purification technologies. Traditional photothermal water evaporation heats the water as a whole, and water evaporation only occurs at the gas-liquid interface, so the thermal utilization rate of this method is low.

[0004] In the past decade, a solar interfacial heating method has been developed to improve evaporation efficiency by localizing heat at the gas-liquid interface. Specifically, it is necessary to meet the following conditions: high absorptivity of the absorbing surface, efficient photothermal conversion of the incident light, thermal localization on the evaporation surface, and effective transport of water from the bulk phase to the thermally localized layer.

[0005] At present, heat exchange between the solar absorber and the water to be treated is carried out through a single heat transfer mode, and the transfer efficiency needs to be improved. Summary of the invention

[0006] To solve the above problems, the embodiments of the present application provide an optical Janus film, a preparation method and application thereof, so as to overcome or at least partially overcome the deficiencies of the prior art.

[0007] In a first aspect, an embodiment of the present application provides an optical Janus film, wherein the upper and lower surfaces of the optical Janus film have micro-nano structures of different sizes, wherein the micro-nano structures include irregular polymer cones and conical holes formed between the irregular polymer cones; wherein the upper surface has a metal coating.

[0008] Optionally, in the above optical Janus film, the average thickness of the metal coating is greater than 50 nm.

[0009] Optionally, in the above-mentioned optical Janus film, the metal coating is formed by at least one of gold, silver, copper, aluminum, palladium, cobalt, chromium, iron, indium, molybdenum, niobium, nickel, lead, platinum, tin, tantalum, vanadium, tungsten, zinc, manganese, antimony, bismuth, and germanium.

[0010] Optionally, in the above optical Janus film, the polymer substrate of the optical Janus film is selected from at least one of polyethylene terephthalate, polyimide, and polycarbonate.

[0011] Optionally, in the above optical Janus film, the aspect ratio of the irregular polymer cone is greater than 20; and the depth-to-width ratio of the cone hole is greater than 20.

[0012] In a second aspect, the present application also provides a method for preparing the above-mentioned optical Janus film, the method comprising:

[0013] The substrate preparation step comprises: irradiating the upper surface and the lower surface of the polymer substrate respectively with high-energy heavy ion beams of different radiation fluxes to cause track damage to the upper surface and the lower surface; and placing the irradiated polymer substrate in an etching solution for etching to form cone holes and irregular polymer cones;

[0014] Metal structure preparation steps: depositing a metal coating on the upper surface of the etched polymer substrate to obtain an optical Janus film.

[0015] Optionally, in the above-mentioned method for preparing an optical Janus film, the polymer substrate is selected from at least one of polyethylene terephthalate, polyimide, and polycarbonate;

[0016] The polymer substrate has a thickness greater than 200 μm.

[0017] Optionally, in the above-mentioned method for preparing an optical Janus film, in the substrate preparation step, if the polymer substrate is selected from at least one of polyethylene terephthalate and polycarbonate, the etching solution is a first mixed solution of a first sodium hydroxide aqueous solution and methanol in any proportion, wherein the concentration of the first sodium hydroxide aqueous solution is 2.5 to 9 mol / L;

[0018] If the polymer substrate comprises polyimide, the etching solution is a second mixed solution of a second sodium hydroxide aqueous solution and sodium hypochlorite in any ratio, wherein the concentration of the second sodium hydroxide aqueous solution is 2.5 to 9 mol / L.

[0019] Optionally, in the above-mentioned method for preparing an optical Janus film, in the substrate preparation step, the concentration of the first sodium hydroxide aqueous solution is 9 mol / L, and the content of the methanol is 95%;

[0020] The concentration of the second sodium hydroxide aqueous solution is 5 mol / L, and the content of the sodium hypochlorite is 90%.

[0021] Optionally, in the above-mentioned method for preparing the optical Janus film, in the substrate preparation step, the etching is performed in a water bath heating environment, the water bath temperature is 25° C.-70° C., and the etching time is 1 h-10 h.

[0022] Optionally, in the above-mentioned method for preparing the optical Janus film, in the substrate preparation step, the high-energy heavy ions are selected from 86 Kr, 129 Xe, 183 Ta and 209 At least one of Bi; and the ion energy of the high-energy heavy ions is greater than 1000MeV.

[0023] Optionally, in the above-mentioned method for preparing the optical Janus film, in the substrate preparation step, the radiation fluence of the upper surface is 5×10 8 ions / cm 2 ~5×10 9 ions / cm 2 ;

[0024] The radiation flux of the lower surface is 1×10 7 ions / cm 2 ~1×10 8 ions / cm 2 .

[0025] Optionally, in the above-mentioned method for preparing the optical Janus film, in the metal structure preparation step, the deposition of the metal coating is performed by any one of magnetron sputtering, vacuum evaporation, ion plating, atomic layer deposition, and electroless chemical deposition.

[0026] Optionally, in the above-mentioned method for preparing the optical Janus film, the average thickness of the metal coating is greater than 50 nm.

[0027] Optionally, in the above-mentioned method for preparing the optical Janus film, the metal coating is formed by at least one of gold, silver, copper, aluminum, palladium, cobalt, chromium, iron, indium, molybdenum, niobium, nickel, lead, platinum, tin, tantalum, vanadium, tungsten, zinc, manganese, antimony, bismuth, and germanium.

[0028] Optionally, in the above-mentioned method for preparing the optical Janus film, in the micro-nano structure of the prepared optical Janus film, the aspect ratio of the irregular polymer cone is greater than 20, and the depth-to-width ratio of the cone hole is greater than 20.

[0029] In a third aspect, the embodiments of the present application further provide an application of any of the above optical Janus films or an optical Janus film prepared by any of the above optical Janus film preparation methods in solar water evaporation.

[0030] Optionally, in the above application, solar water evaporation is performed according to the following steps:

[0031] The solar water evaporation device is placed under the sun, wherein the solar water evaporation device comprises, from top to bottom, a water collecting tank and a water supply tank, and a transparent protective cover, a heat-insulating foam board, an optical Janus film, and a water-drawing strip are arranged on the top of the water collecting tank from top to bottom;

[0032] The water supply tank is filled with water, and after a preset period of time, water is collected from the water collection tank of the solar water evaporation device.

[0033] At least one of the above technical solutions adopted in the embodiments of the present application can achieve the following beneficial effects:

[0034] The optical Janus film of the present invention has the characteristic of selectively absorbing sunlight on its upper surface and has the function of radiation heating on its lower surface. When used for solar water evaporation, it has a dual heat exchange mode of heat conduction and heat radiation, which can improve the utilization rate of sunlight and the heat transfer efficiency. The optical Janus film of the present application is flexible, can be applied to non-flat surfaces, has a simple preparation method, and can be prepared on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0036] Figure 1 A schematic structural diagram of an optical Janus film according to an embodiment of the present application is shown;

[0037] Figure 2 The scanning electron microscope image of the micro-nano structure on the upper surface of the optical Janus film obtained in Example 1 of the present application is shown;

[0038] Figure 3 The scanning electron microscope image of the micro-nano structure of the lower surface of the optical Janus film obtained in Example 1 of the present application is shown;

[0039] Figure 4 shows the absorption spectrum of the upper surface of the optical Janus film obtained in Example 1 of the present application;

[0040] Figure 5 shows the absorption spectrum of the lower surface of the optical Janus film obtained in Example 1 of the present application;

[0041] Figure 6 A schematic diagram showing the use of an optical Janus film according to an embodiment of the present application for solar water evaporation is shown. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the specific embodiments of the present application and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

[0043] Janus membrane is a kind of Janus interface material. In a narrow sense, it requires opposite physical and chemical properties on both sides of the membrane. In a broad sense, the upper and lower surfaces of the membrane have different physical and chemical properties. Janus film has become one of the research hotspots in the field of materials in the past two decades due to its unique structure, multiple performance integration and broad application prospects. It uses the different properties on both sides of the membrane to achieve a series of new functions. For example, hydrophilic / hydrophobic membranes are used in processes involving two-phase interfaces (such as oil-water separation, bubbling, emulsification, demulsification, etc.), which can effectively reduce the energy consumption of membrane processes involving two-phase interfaces; positive / negative type Janus membranes can be used in concentration polarization power generation and high-efficiency nanofiltration processes. Taking concentration polarization power generation as an example, the significance of the Janus system is that it can effectively achieve the selective permeation of a certain type of charged ion, which cannot be effectively achieved using traditional membranes.

[0044] The present application utilizes the characteristics of the Janus film and, in the field of optics, provides a Janus film having different optical properties on the upper and lower surfaces, which can be used in the field of solar water evaporation technology.

[0045] The present application provides an optical Janus film, wherein the upper and lower surfaces of the optical Janus film have micro-nano structures of different sizes, wherein the micro-nano structures include irregular polymer cones and cone holes formed between the irregular polymer cones; wherein the upper surface has a metal coating.

[0046] Figure 1 A schematic diagram of the structure of an optical Janus film according to an embodiment of the present application is shown. Figure 1It can be seen that the upper and lower surfaces of the optical Jauns film have micro-nano structures of different sizes. The micro-nano structural units include irregular polymer cones and conical holes. The irregular polymer cones are connected by conical holes with the cone tips pointing downward. The irregular polymer cones have a large aspect ratio, and the conical holes have a large depth-to-width ratio. This structure has no obvious platform area (the platform will reflect light upward and affect the light absorption effect), and has an excellent light trapping effect.

[0047] The upper surface of the optical Jauns film has a metal coating. Due to the three-dimensional conformal effect, the metal coating forms an irregular hollow metal cone and metal conical hole structure that "replicates" the micron structure of the upper surface.

[0048] The upper and lower surfaces of the optical Jauns film have different absorption / emission characteristics. In order to improve the utilization rate of sunlight and the heat transfer efficiency in solar interface water evaporation, the upper surface of the optical Jauns film has strong absorption in the solar spectrum range, efficiently converting sunlight into heat, and at the same time has a lower emissivity in the mid- and far-infrared bands to reduce radiation heat dissipation; the lower surface has extremely high emissivity (up to 99.9%) in the visible to mid- and far-infrared bands, and has a radiation heating function.

[0049] It should be noted that according to Kirchhoff's radiation law, the hemispherical spectral emissivity of any object (for a Lambertian body, the hemispherical emissivity, hemispherical spectral emissivity and directional emissivity are equal to each other) is equal to the spectral absorptivity of the object at the same temperature, so the emissivity at a certain wavelength mentioned in this application is equal to the absorptivity at that wavelength.

[0050] The absorption / emission characteristics of the upper and lower surfaces of the optical Jauns film of the present application can be flexibly adjusted by the surface micro-nano structure and the intrinsic absorption of the material.

[0051] Preferably, in some embodiments, the average thickness of the metal coating is greater than 50 nm.

[0052] Preferably, in some embodiments, the metal coating is formed by at least one of gold, silver, copper, aluminum, palladium, cobalt, chromium, iron, indium, molybdenum, niobium, nickel, lead, platinum, tin, tantalum, vanadium, tungsten, zinc, manganese, antimony, bismuth, and germanium.

[0053] Preferably, in some embodiments, the polymer substrate of the optical Jauns film is selected from at least one of polyethylene terephthalate, polyimide, and polycarbonate.

[0054] Preferably, in some embodiments, the aspect ratio of the irregular polymer cone is greater than 20; the depth-to-width ratio of the cone hole is greater than 20.

[0055] The embodiment of the present application also provides a method for preparing an optical Janus film, the method comprising a substrate preparation step S110 to a metal structure preparation step S120:

[0056] Substrate preparation step S110: using high-energy heavy ion beams with different radiation doses to irradiate the upper surface and lower surface of the polymer substrate respectively to cause track damage to the upper surface and the lower surface; and placing the irradiated polymer substrate into an etching solution for etching to form conical holes and irregular polymer cones.

[0057] First, a substrate with irregular polymer cones and cone holes is prepared. A high-energy heavy ion beam is used to sequentially irradiate the upper and lower surfaces of the polymer substrate to break the chemical bonds on the ion path, generating a latent track damage area with a diameter of several nanometers on the path. The polymer substrate is etched with a special etching solution. Due to the breaking of chemical bonds in the latent track area, many free radicals are formed, so the etching rate V along the track direction is t Much larger than the bulk etch rate V b , forming a tapered hole with a large aspect ratio, where the body etching rate V b It can be understood as the average rate of etching in all directions in the bulk of the polymer substrate. In some embodiments, it can be characterized by the rate of decrease of the thickness of the polymer substrate before and after etching, that is, the ratio of the difference in the thickness or average thickness of the polymer substrate before and after etching to the etching time. As the etching time increases, the bottoms of the cone holes overlap, and the platform area between the cone holes gradually decreases, eventually forming an irregular polymer cone structure.

[0058] The final complex micro-nanostructure is composed of two types of structural units: irregular polymer cones with large aspect ratios and conical holes between irregular polymer cones. Depending on the specific application requirements, the irradiation injection on the upper and lower surfaces can be different, corresponding to different structural sizes, which ultimately affects the absorption / emission characteristics of the surface.

[0059] In some embodiments, in step S110, the polymer substrate may be a mixed polymer formed by one or more of polyethylene terephthalate (PET), polyimide (PI) and polycarbonate (PC), and the thickness of the polymer substrate is preferably greater than 200 μm, so as to ensure that the ions on the upper and lower surfaces of the polymer substrate will not penetrate the entire polymer substrate during subsequent irradiation, thereby affecting the irradiation effect of the other surface.

[0060] In some embodiments, in step S110, the high energy heavy ions are preferably 86 Kr, 129 Xe, 183 Ta and 209In some embodiments, preferably, the ion energy is greater than 1000 MeV. If the ion energy is too small, the damage in the polymer substrate is limited, and the cone holes formed by subsequent etching are of different sizes and have a small depth-to-width ratio, especially for the lower surface, which is not conducive to achieving a wide spectrum and high emissivity.

[0061] In some embodiments, in order to achieve selective absorption of sunlight by the upper surface and high emissivity of the lower surface over a wide spectrum, the upper surface requires a larger irradiation flux, corresponding to a smaller substrate surface structure size. Therefore, the irradiation flux of the upper surface of the polymer substrate is preferably 5×10 8 ions / cm 2 -5×10 9 ions / cm 2 The lower surface requires a smaller irradiation flux, corresponding to a larger substrate surface structure size. The radiation flux of the lower surface of the polymer substrate is preferably 1×10 7 ions / cm 2 -1×10 8 ions / cm 2 .

[0062] In some embodiments, in the above-mentioned method for preparing an optical Janus film, in the substrate preparation step, if the polymer substrate is selected from at least one of polyethylene terephthalate and polycarbonate, the etching solution is a first mixed solution of a first sodium hydroxide aqueous solution and methanol in any proportion, wherein the concentration of the first sodium hydroxide aqueous solution is 2.5 to 9 mol / L; if the polymer substrate contains polyimide, the etching solution is a second mixed solution of a second sodium hydroxide aqueous solution and sodium hypochlorite in any proportion, wherein the concentration of the second sodium hydroxide aqueous solution is 2.5 to 9 mol / L.

[0063] Preferably, in some embodiments, the concentration of the first sodium hydroxide aqueous solution is 9 mol / L, and the mass content of the methanol in the first mixed liquid is 95%; the concentration of the second sodium hydroxide aqueous solution is 5 mol / L, and the mass content of the sodium hypochlorite in the second mixed liquid is 90%.

[0064] In some embodiments, in step S110, for different polymer films, the composition and ratio of the etching solution are also different. For PC and PET, the etching solution is preferably a mixture of sodium hydroxide (NaOH) aqueous solution and methanol, the sodium hydroxide (NaOH) aqueous solution is recorded as the first sodium hydroxide aqueous solution, and the mixed solution is recorded as the first mixed solution, wherein the first sodium hydroxide aqueous solution is preferably 2.5-9 mol / L, and methanol can be of analytical grade from any manufacturer on the market. The first sodium hydroxide aqueous solution and methanol can be mixed in any proportion, wherein the content of one of the first sodium hydroxide aqueous solution and methanol can be zero, preferably not zero; more preferably, the first mixed solution of the first NaOH aqueous solution and methanol of 9 mol / L, wherein methanol accounts for 95% of the first mixed solution; for PI, the etching solution is preferably a mixture of sodium hydroxide (NaOH) aqueous solution and sodium hypochlorite, the sodium hydroxide (NaOH) aqueous solution is recorded as the second sodium hydroxide aqueous solution, and the mixed solution is recorded as the second mixed solution, wherein the second sodium hydroxide aqueous solution is preferably 2.5-9 mol / L The NaOH aqueous solution and sodium hypochlorite (NaClO) can be of analytical grade from any commercial manufacturer. The second sodium hydroxide aqueous solution and sodium hypochlorite can be mixed in any proportion, wherein the content of one of the second sodium hydroxide aqueous solution and sodium hypochlorite can be zero, preferably not zero; more preferably, a second mixed solution of 5 mol / L NaOH aqueous solution and analytical grade NaClO can be used, wherein the mass content of NaClO in the second mixed solution is 90%.

[0065] In some embodiments, in step S110, etching is performed in a water bath heating environment, the etching temperature is between 25°C and 70°C, the etching time can be determined according to the etching solution ratio and the etching temperature, and the etching time is preferably between 1h and 10h.

[0066] Metal structure preparation step S120: depositing a metal coating on the upper surface of the etched polymer substrate to obtain an optical Janus film.

[0067] After preparing a substrate with irregular polymer cones and cone hole structures, a metal structure is prepared on the upper surface of the etched polymer substrate. Specifically, a layer of metal is deposited on the upper surface to form an irregular hollow metal cone and metal cone hole structure as a sunlight selective absorption layer, and the lower surface is used as a wide-spectrum thermal radiation layer to obtain an optical Jauns film that can improve the sunlight utilization rate and heat transfer efficiency in solar interface water evaporation.

[0068] In some embodiments, in the above-mentioned metal structure preparation step, the deposition of the metal coating can be carried out by any method such as magnetron sputtering, vacuum evaporation, ion plating, atomic layer deposition, electroless chemical deposition, etc.

[0069] In some embodiments, in the above-mentioned metal structure preparation step, preferably, the average thickness of the metal coating is greater than 50 nm.

[0070] In some embodiments, in the above-mentioned metal structure preparation step, the material of the metal coating can be a single metal such as gold, silver, copper, aluminum, palladium, cobalt, chromium, iron, indium, molybdenum, niobium, nickel, lead, platinum, tin, tantalum, vanadium, tungsten, zinc, manganese, antimony, bismuth, germanium, etc., or it can be an alloy composed of the above-mentioned metals, such as nickel-chromium, nickel-iron, titanium-aluminum and other alloys.

[0071] The optical Janus film obtained by any of the above optical Janus film preparation methods has an irregular polymer cone with an aspect ratio greater than 20 and a cone hole with a depth-to-width ratio greater than 20.

[0072] The method of using the above-mentioned optical Janus film for solar water evaporation is as follows: the upper surface of the optical Janus film in the present application can efficiently absorb sunlight and convert sunlight into thermal energy, and the upper surface has a low infrared emissivity, and the upward thermal radiation is small, reducing heat loss; the lower surface has extremely high emissivity in the visible to mid- and far-infrared bands, and has strong thermal radiation downward.

[0073] Janus membranes can be installed in solar water evaporation devices, please refer to Figure 6 The solar water evaporation device includes, from top to bottom, a water collecting tank and a water supply tank; a transparent protective cover, a heat-insulating foam board, an optical Janus film, and a water-drawing strip are arranged on the top of the water collecting tank from top to bottom; wherein the water-drawing strip is preferably made of non-woven fabric.

[0074] The water supply tank is filled with water, and after a preset period of time, water can be collected from the water collection tank of the solar water evaporation device.

[0075] As for how to fill the water supply tank with water, the water in the water supply source can be pumped into the water supply tank of the solar water evaporation device, wherein the water supply source can be a reservoir of a water treatment plant; it can also be a river, lake, sea water, etc. in nature.

[0076] In some actual scenarios, the solar water evaporation device may not be provided with a water supply tank. In this case, the solar water evaporation device only includes a water collection tank; a transparent protective cover, a heat-insulating foam board, an optical Janus film, and a water-drawing strip are arranged on the top of the water collection tank from top to bottom; wherein the water-drawing strip is preferably made of non-woven fabric. When in use, the solar water evaporation device can be directly placed in the water supply source, which can be understood as the water supply source can be used as the water supply tank of the solar water evaporation device. The water supply source is the same as the water reservoir of the water treatment plant mentioned above; it can also be a river, lake, sea water, etc. in nature.

[0077] The optical Janus film is in contact with the water-drawing strip, which draws a small amount of water to the heating area through capillary action; the optical Janus film transfers heat to the water-drawing strip through the dual heat exchange modes of heat conduction and heat radiation (heat convection heat exchange also exists, but the proportion is small), so that the water in it is heated and evaporated, and condensed in the collection tank below. In addition, the interface heating area is surrounded by thermal insulation materials, and the optical Janus film is placed above a transparent protective cover, with an air layer between the two to reduce heat loss.

[0078] Example 1

[0079] The preparation method of the optical Janus film is as follows:

[0080] (1) The upper and lower surfaces of a 500 μm thick PC film (polymer substrate) were irradiated in sequence by the TR5 irradiation terminal of the Heavy Ion Research Facility Lanzhou (HIRFL) of the Institute of Modern Physics, Chinese Academy of Sciences. The irradiation ions were Xe with an ion energy of 2500 MeV and an upper surface irradiation dose of 5×10 8 ions / cm 2 The irradiation dose on the lower surface is 1×10 7 ions / cm 2 . Place the irradiated polymer substrate in an etching solution to ensure that the upper and lower surfaces of the polymer substrate are in full contact with the etching solution. The etching solution is a first mixture of a first NaOH aqueous solution and methanol, wherein the concentration of the first NaOH aqueous solution is 9 mol / L, and the methanol is of analytical grade. The mass content of methanol in the first mixture is 95%. The temperature is maintained at 25°C in a water bath and etching is performed for 8 hours. Then take the polymer substrate out of the etching solution, rinse it twice with deionized water to remove the residual etching solution and adsorbed particles on the surface, rinse it once with anhydrous ethanol, and finally rinse it again with deionized water and suspend it to dry naturally. Finally, a polymer substrate with a micro-nano structure is obtained, and the upper surface structure is as follows: Figure 2 As shown, the lower surface structure is Figure 3 As shown, from Figure 2 and Figure 3 It can be seen that the micro-nano structure of the polymer substrate is composed of two types of structural units: conical holes with a large aspect ratio and irregular polymer cones with a large length-to-diameter ratio. In addition, the size of the micro-nano structure on the upper surface is larger than that on the lower surface.

[0081] (2) The etched polymer substrate is placed in a magnetron sputtering coating apparatus, with the upper surface (having a relatively smaller micro-nano structure, the same below) facing the sputtering target, the target material is selected as Ag, the sputtering current is set to 10 mA, the coating time is 20 min, the surface coating thickness is about 200 nm, and the polymer substrate with the metal coating is taken out after the sputtering is completed. An optical Janus film with a solar light heat conversion function on the upper surface and a radiation heating function on the lower surface is obtained.

[0082] Figure 4 The absorption spectrum of the upper surface of the optical Janus film obtained in Example 1 of the present application is shown. Figure 4 From the spectral results shown, it can be seen that the upper surface of the optical Janus film has strong absorption in the solar spectrum range of 300-2000nm, which can convert sunlight into heat energy, and has a smaller absorption rate in the mid- and far-infrared bands of 5-20μm, that is, it has a lower infrared emissivity, which can reduce radiative heat dissipation.

[0083] Figure 5 The absorption spectrum of the lower surface of the optical Janus film obtained in Example 1 of the present application is shown. Figure 5 From the spectral results shown, it can be seen that the lower surface of the optical Janus film has a wide spectrum of ultra-high emissivity in the 0.3-16μm band, that is, it has efficient thermal radiation.

[0084] It should be noted that, taking a 50°C black body as an example, its black body radiation peak is about 9 μm (located in the high emissivity spectrum of the lower surface of the optical Janus film obtained in Example 1), and its total radiation emittance is about 617 W / m 2 ,The infrared emissivity of the optical Janus film is close to that of an ideal black body, so its lower surface has strong thermal radiation, that is, it has a radiation heating function.

[0085] Example 2

[0086] The preparation method of the optical Janus film is as follows:

[0087] (1) The upper and lower surfaces of a 500 μm thick PI film (polymer substrate) were irradiated in sequence by the TR5 irradiation terminal of the Heavy Ion Research Facility (HIRFL) of the Institute of Modern Physics, Chinese Academy of Sciences. The irradiation ions were Ta, the ion energy was 2900 MeV, and the upper surface irradiation dose was 5×10 9 ions / cm 2 The irradiation dose on the lower surface is 1×10 8 ions / cm 2 . Place the irradiated polymer substrate in an etching solution to ensure that the upper and lower surfaces of the membrane are in full contact with the etching solution. The etching solution is a second mixture of a second NaOH aqueous solution and NaClO, wherein the concentration of the second NaOH aqueous solution is 5 mol / L, NaClO is of analytical grade, and the mass content of NaClO in the second mixture is 90%. Etching is performed in a water bath at 50°C for 4 hours. Then take the polymer substrate out of the etching solution, rinse it twice with deionized water to remove the etching solution remaining on the surface, rinse it once with anhydrous ethanol, and finally rinse it again with deionized water and hang it to dry naturally.

[0088] (2) The etched polymer substrate is placed in a magnetron sputtering coating apparatus with its upper surface facing the sputtering target. The target material is selected as Au, the sputtering current is set to 10 mA, and the coating time is 30 min. After the sputtering is completed, the polymer substrate is taken out to obtain an optical Janus film.

[0089] Example 3

[0090] The preparation method of the optical Janus film is as follows:

[0091] (1) The upper and lower surfaces of a 500 μm thick PI film (polymer substrate) were irradiated in sequence by the TR5 irradiation terminal of the Heavy Ion Research Facility Lanzhou (HIRFL) of the Institute of Modern Physics, Chinese Academy of Sciences. The irradiation ions were Bi, the ion energy was 1980 MeV, and the upper surface irradiation dose was 1×10 9 ions / cm 2 The irradiation dose of the lower surface is 5×10 7 ions / cm 2 . Place the irradiated polymer substrate in an etching solution to ensure that the upper and lower surfaces of the film are in full contact with the etching solution. The etching solution is a second mixture of a second NaOH aqueous solution and NaClO, wherein the concentration of the second NaOH aqueous solution is 2.5 mol / L, NaClO is of analytical grade, and the mass content of NaClO in the second mixture is 50%. Etching is performed in a water bath at 70°C for 8 hours. Then take the polymer substrate out of the etching solution, rinse it twice with deionized water to remove the etching solution remaining on the surface, rinse it once with anhydrous ethanol, and finally rinse it again with deionized water and hang it to dry naturally.

[0092] (2) The etched polymer substrate is placed in a magnetron sputtering coating apparatus with its upper surface facing the sputtering target. The target material is selected as Cu, the sputtering current is set to 5 mA, and the coating time is 30 min. After the sputtering is completed, the substrate is taken out to obtain an optical Janus film.

[0093] Example 4

[0094] The preparation method of the optical Janus film is as follows:

[0095] (1) The upper and lower surfaces of a 200 μm thick PET film (polymer substrate) were irradiated in sequence by the TR5 irradiation terminal of the Heavy Ion Research Facility Lanzhou (HIRFL) of the Institute of Modern Physics, Chinese Academy of Sciences. The irradiation ions were Kr, the ion energy was 1000 MeV, and the upper surface irradiation dose was 5×10 9 ions / cm 2 The irradiation dose on the lower surface is 1×10 7 ions / cm 2. Place the irradiated polymer substrate in an etching solution to ensure that the upper and lower surfaces of the film are in full contact with the etching solution. The etching solution is a first mixture of a first NaOH aqueous solution and methanol, wherein the concentration of the first NaOH aqueous solution is 5 mol / L, methanol is of analytical grade, and the mass content of methanol in the first mixture is 50%. Etching is performed in a water bath at 30°C for 4 hours. Then take the polymer substrate out of the etching solution, rinse it twice with deionized water to remove the etching solution remaining on the surface, rinse it once with anhydrous ethanol, and finally rinse it again with deionized water and hang it to dry naturally.

[0096] (2) The etched polymer substrate is placed in a magnetron sputtering coating apparatus with its upper surface facing the sputtering target. The target material is selected as Al, the sputtering current is set to 100 mA, and the coating time is 20 min. After the sputtering is completed, the polymer substrate is taken out to obtain an optical Janus film.

[0097] Example 5

[0098] The method of using optical Janus film for solar water evaporation is as follows:

[0099] The optical Janus film with solar heat conversion function on the upper surface and radiation heating function on the lower surface is obtained through the preparation process of Example 1. Figure 6 In the solar water evaporation device shown, seawater is pumped into the water supply tank. The device includes, from top to bottom, a transparent protective cover, a heat-insulating foam board, an optical Janus film, a water-drawing strip, a water collection tank, and a water supply tank. The water supply tank can be replaced by a natural water body. The solar water evaporation device can be directly fixed on the surface of a water body such as a salt lake or the sea, and can be used in the fields of seawater desalination and sewage purification.

[0100] Among them, the upper surface of the optical Janus film receives sunlight and converts it into heat energy to form an interface heating area. There is an air layer between the optical Janus film and the transparent protective cover to reduce heat loss. The water-drawing strip is made of non-woven fabric and is in direct contact with the lower surface of the optical Janus film. A small amount of water is drawn to the heating area through capillary action. The lower surface of the optical Janus film transfers heat to the water-drawing strip through a dual heat exchange mode of heat conduction and heat radiation, so that the water in it is heated and evaporated, and the water vapor is condensed in the water collection tank below and collected. The water collection tank is made of metal and has good thermal conductivity. The water collection tank floats on the low-temperature water surface in the water supply tank. The low-temperature water body of the water supply tank serves as the cold source of the water collection tank to ensure the rapid condensation of water vapor.

[0101] After a period of time, the water can be collected from the water collection tank.

[0102] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.

Claims

1. An optical Janus film, characterized in that: The upper surface and the lower surface of the optical Jauns film have micro-nano structures of different sizes, and the micro-nano structures include irregular polymer cones and cone holes formed between the irregular polymer cones; wherein the upper surface has a metal coating; The upper surface of the optical Janus film can absorb sunlight and has a low infrared emissivity; the lower surface of the optical Janus film has a high emissivity in the visible to mid- and far-infrared bands.

2. The optical Janus film according to claim 1, characterized in that: The average thickness of the metal coating is greater than 50 nm.

3. The optical Janus film according to claim 2, characterized in that: The metal plating layer is formed of at least one of gold, silver, copper, aluminum, palladium, cobalt, chromium, iron, indium, molybdenum, niobium, nickel, lead, platinum, tin, tantalum, vanadium, tungsten, zinc, manganese, antimony, bismuth, and germanium.

4. The optical Janus film according to claim 1, characterized in that: The polymer substrate of the optical Jauns film is selected from at least one of polyethylene terephthalate, polyimide, and polycarbonate.

5. The optical Janus film according to any one of claims 1 to 4, characterized in that: The aspect ratio of the irregular polymer cone is greater than 20; the depth-to-width ratio of the cone hole is greater than 20.

6. A method for preparing the optical Janus film according to claim 1, characterized in that: The method comprises: The substrate preparation step comprises: irradiating the upper surface and the lower surface of the polymer substrate respectively with high-energy heavy ion beams of different radiation fluxes to cause track damage to the upper surface and the lower surface; and placing the irradiated polymer substrate in an etching solution for etching to form cone holes and irregular polymer cones; The metal structure preparation step is as follows: a metal coating is deposited on the upper surface of the etched polymer substrate to obtain an optical Janus film; The upper surface of the optical Janus film can absorb sunlight and has a low infrared emissivity; the lower surface of the optical Janus film has a high emissivity in the visible to mid- and far-infrared bands.

7. The method for preparing an optical Janus film according to claim 6, characterized in that: The polymer substrate is selected from at least one of polyethylene terephthalate, polyimide, and polycarbonate; The polymer substrate has a thickness greater than 200 μm.

8. The method for preparing an optical Janus film according to claim 7, characterized in that: In the substrate preparation step, if the polymer substrate is selected from at least one of polyethylene terephthalate and polycarbonate, the etching solution is a first mixed solution of a first sodium hydroxide aqueous solution and methanol in any proportion, wherein the concentration of the first sodium hydroxide aqueous solution is 2.5 to 9 mol / L; If the polymer substrate comprises polyimide, the etching solution is a second mixed solution of a second sodium hydroxide aqueous solution and sodium hypochlorite in any ratio, wherein the concentration of the second sodium hydroxide aqueous solution is 2.5 to 9 mol / L.

9. The method for preparing an optical Janus film according to claim 8, characterized in that: In the substrate preparation step, the concentration of the first sodium hydroxide aqueous solution is 9 mol / L, and the mass content of methanol in the first mixed solution is 95%; The concentration of the second sodium hydroxide aqueous solution is 5 mol / L, and the mass content of the sodium hypochlorite in the second mixed solution is 90%.

10. The method for preparing an optical Janus film according to any one of claims 6 to 9, characterized in that: In the substrate preparation step, the etching is performed in a water bath heating environment, the water bath temperature is 25° C.-70° C., and the etching time is 1 h-10 h.

11. The method for preparing an optical Janus film according to claim 6, characterized in that: In the substrate preparation step, the high energy heavy ions are selected from 86 Kr, 129 Xe, 183 Ta and 209 At least one of Bi; and the ion energy of the high-energy heavy ions is greater than 1000MeV.

12. The method for preparing an optical Janus film according to claim 6 or 11, characterized in that: In the substrate preparation step, the radiation flux of the upper surface is 5×10 8 ions / cm 2 ~5×10 9 ions / cm 2 ; The radiation flux of the lower surface is 1×10 7 ions / cm 2 ~1×10 8 ions / cm 2 .

13. The method for preparing an optical Janus film according to claim 6, characterized in that: In the metal structure preparation step, the metal coating is deposited by any one of magnetron sputtering, vacuum evaporation, ion plating, atomic layer deposition, and electroless chemical deposition.

14. The method for preparing an optical Janus film according to claim 6 or 13, characterized in that: The average thickness of the metal coating is greater than 50 nm.

15. The method for preparing an optical Janus film according to claim 6 or 13, characterized in that: The metal plating layer is formed of at least one of gold, silver, copper, aluminum, palladium, cobalt, chromium, iron, indium, molybdenum, niobium, nickel, lead, platinum, tin, tantalum, vanadium, tungsten, zinc, manganese, antimony, bismuth, and germanium.

16. The method for preparing an optical Janus film according to claim 6, characterized in that: The optical Janus film prepared by the method for preparing an optical Janus film according to claim 6 has an aspect ratio of irregular polymer cones greater than 20; and a depth-to-width ratio of the cone hole greater than 20.

17. Use of the optical Janus film according to any one of claims 1 to 5 or the optical Janus film prepared by the method for preparing the optical Janus film according to any one of claims 6 to 9 in solar water evaporation.

18. The use according to claim 17, characterized in that Solar water evaporation is carried out according to the following steps: The solar water evaporation device is placed under the sun, wherein the solar water evaporation device comprises, from top to bottom, a water collecting tank and a water supply tank, and a transparent protective cover, a heat-insulating foam board, an optical Janus film, and a water-drawing strip are arranged on the top of the water collecting tank from top to bottom; The water supply tank is filled with water, and after a preset period of time, the water is collected from the water collection tank of the solar water evaporation device.